Teori Identitas Sosial, Stereotipe, dan Prasangka dalam Fenomena Kontemporer: Kajian Literatur - Rahmawati, Afika Ira; S., Neviyarni (Lembaga Yasin AlSys, 2026)
Social identity, stereotypes, and prejudice are key concepts in social psychology that play a major role in shaping patterns of interaction between individuals and groups, and in the current context of globalization and digitalization the dynamics of group identity and the potential emergence of stereotypes and prejudice are becoming increasingly complex. This study aims to systematically examine theories of social identity, stereotypes, and prejudice and their applications in contemporary social phenomena through a literature review approach. The method used is a literature study by reviewing various relevant scientific sources on the concepts of social identity, stereotypes, and prejudice, then analyzing them by identifying the main themes, key concepts, and patterns of relationships among concepts that emerge in previous studies. The results of the review show that social identity plays an important role in forming ingroup and outgroup categories, which subsequently influence the ways individuals evaluate, treat, and interact with other groups. Further discussion reveals that stereotypes and prejudice are influenced not only by individual cognitive factors, but also by social and cultural contexts and the role of the media, especially in the era of modern social life that is strongly influenced by digital media. These findings affirm that a comprehensive understanding of theories of social identity, stereotypes, and prejudice becomes an important foundation for managing diversity and building more inclusive social relations in contemporary society.